Berger, Carol. 2022. The Child Soldiers of Africa’s Red Army: The Role of Social Process and Routinised Violence in South Sudan’s Military. London: Routledge. 225 pp., index, bibliography. ISBN: 9780367742607 - Sjoerd Zanen (Modern Africa)
Erratum for hard copy: On page 105 the year of the internal South Sudanese civil war should be 2013, not 1913.